MANAJEMEN KELOMPOK USAHA BERSAMA (KUBE) DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DI DESA TOLANGO KECAMATAN ANGGREK KABUPATEN GORONTALO UTARA - A Pakaya, Widyawati; Rachman, Ellys; Antu, Yahya (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2023)
This research aims to determine the management of joint business groups (kube) in increasing community income in Tolango Village, Anggrek District, North Gorontalo Regency. The research method used is descriptive qualitative. The research results show that the commitment of the Mekar Sari group members is not very good. This can be seen from the low work ethic and poor cohesiveness of the group members. The managerial abilities of the Mekar Sari Group Chair are no longer working well. This can be seen from the inability to direct its members. Institutional support for the Mekar Sari Joint Business Group (Kube) is optimal. This can be seen from the existence of government assistance, namely providing business capital assistance and advocacy or mentoring.